Optimal forest management under climate change variability - Rosa, Renato; Simas, Constança; Ataíde, Rodrigo; Soares, Paula; Tomé, Margarida (Ecological economics, 2024)
Ecosystems are likely to be severely affected by climate change. While the literature on this subject focuses primarily on climate variable means, increasing evidence has been gathered on the importance of changes in climate variability in determining ecosystem impacts. In this context, forests play a significant role. While, on the one hand, forests have often been identified to be a key element in mitigating greenhouse gas emissions, on the other, forests are also affected by changes in climate. However, the number of studies on optimal forest management under climate change remains limited and has overlooked the role of climate variability. This paper adds to that literature by developing a coupled ecological-economic forest stand model in which forest dynamics are a function of monthly climate variables. We show that accounting for changes in climate variability substantially changes earlier findings. In particular, ignoring climate variability may fail to adequately account for changes in optimal harvest age and lead to erroneous conclusions regarding the effects of climate change on forested land value.